Temporal trends and geographic disparities in thyroid cancer burden: a global analysis from 1990 to 2021 - Zhao, Zuzhi; Fan, Yinghao; Sun, Peng; Zhang, Suqin; Xu, Mengfei; Li, Jianhua; Xu, Pengfei (Frontiers in Nutrition, 2025)
BackgroundOver the past 40 years, the global incidence of thyroid cancer has increased steadily. This study aimed to update the evaluation of thyroid cancer prevalence, incidence, mortality, and Disability–Adjusted Life Years (DALYs) rates from 1990 to 2021, with a focus on integrating prevalence data. Analyses were stratified by gender, age, and Socio–Demographic Index (SDI) at global, regional, and national levels.MethodsData were obtained from the 2021 Global Burden of Disease, Injuries, and Risk Factors Study (GBD). The estimated annual percentage change (EAPC) was calculated to quantify temporal trends and evaluate age - standardized rates for prevalence (ASPR), incidence (ASIR), mortality (ASDR), and DALYs.ResultsIn 2021, the global thyroid cancer burden was substantial, with 1,987,148.5 cases. From 1990 to 2021, the ASPR increased from 14.9 (95% Uncertainty Interval [UI]: 14.1–16.0) to 23.1 (95% UI: 20.7–25.6) per 100,000 population, with an EAPC of 1.58 (95% UI: 1.44–1.73); the ASIR increased from 2.1 (95% UI: 2–2.2) to 2.9 (95% UI: 2.6–3.2) per 100,000 population, with an EAPC of 1.25 (95% UI: 1.14–1.37); the ASDR declined from 0.6 (95% UI: 0.5–0.6) to 0.5 (95% UI: 0.5–0.6) per 100,000 population, with an EAPC of −0.24 (95% UI: −0.24 – −0.21); the age - standardized DALY rate decreased from 15.2 (95% UI: 14.2–16.8) to 14.6 (95% UI: 12.8–16.1) per 100,000 population, with an EAPC of −0.14 (95% UI: −0.17 – –0.11). Western Sub–Saharan Africa had the lowest rates, while high–income North America had the highest ASPR and ASIR, and Andean Latin America had the highest ASDR. Higher SDI regions showed higher ASPR and ASIR, whereas lower SDI regions had higher ASDR. Saudi Arabia had the highest ASPR and ASIR, and Ethiopia had the highest ASDR and age–standardized DALY rate.ConclusionFrom 1990 to 2021, the global health burden of thyroid cancer increased significantly, with marked geographical disparities. Prevention and control strategies should consider the unequal global distribution of the disease.